Light Chain Multiple Myeloma: A Case of Distinctive Presentations - Henrika, Fify; Wisdharilla, Reiva (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Multiple Myeloma (MM) is a malignancy of immunoglobulin-producing plasma cells. Lambda Light Chain Multiple Myeloma (LCMM) is a less common type of MM with a more aggressive course, which presents a diagnostic challenge due to the absence of typical M-spike on screening and unspecific manifestations. This case presented an initially misdiagnosed patient, who had an uncommon light chain pattern on electrophoresis, atypical plasmocytes in bone marrow smear, particular complications and risks associated with LCMM, and a worse prognosis.